TRACING PRE-ERUPTIVE MAGMA DEGASSING USING (210PB/226RA) DISEQUILIBRIA IN THE VOLCANIC DEPOSITS OF THE 1980-1986 ERUPTION OF MOUNT ST. HELENS - Berlo K.; Blundy J.; Hawkesworth C.; Turner S.; Black S. (My University, 2006)
Disequilibria between210Pb and226Ra can be used to trace magma degassing, because the intermediate nuclides, particularly222Rn, are volatile. Products of the 1980-1986 eruptions of Mount St. Helens have been analysed for (210Pb/226Ra). Both excesses and deficits of210Pb are encountered suggesting rapid gas transfer. The time scale of diffuse, non-eruptive gas escape prior to 1980 as documented by210Pb deficits is on the order of a decade using the model developed by Gauthier and Condomines (Earth Planet. Sci. Lett. 172 (1999) 111-126) for a non-renewed magma chamber and efficient Rn removal. The time required to build-up210Pb excess is much shorter (months) as can be observed from steady increases of (210Pb/226Ra) with time during 1980-1982. The formation of210Pb excess requires both rapid gas transport through the magma and periodic blocking of gas escape routes. Superposed on this time trend is the natural variability of (210Pb/226Ra) in a single eruption caused by tapping magma from various depths. The two time scales of gas transport, to create both210Pb deficits and210Pb excesses, cannot be reconciled in a single event. Rather210Pb deficits are associated with pre-eruptive diffuse degassing, while210Pb excesses document the more vigorous degassing associated with eruption and recharge of the system. © 2006 Elsevier B.V. All rights reserved.
Keywords: DEGASSING; MOUNT ST. HELENS; PB-210; RA-226; TIME SCALES